Oblique penetration mechanism of hybrid composite laminates - Han Meng (De Gruyter, 2021)
Hybrid fiber composites are widely used to improve the anti-penetration performance. Carbon/Kevlar hybrid composites are used in aircrafts and safety devices, thanks to the strong toughness of Kevlar fibers and high strength of carbon fibers. In the present work, the contact force of hybrid composites under oblique impact is derived. The viscoelastic constitutive model of Kevlar layer is investigated and the dissipation energies of composites for different high velocity oblique impacts are simulated. The results show that hybrid composites have good bullet-proof performance, the contact forces are fluctuant in short time and the frictional dissipation energy allows us to prevent penetration.